Influência da estrutura da vegetação de áreas recuperadas pós-mineração em comunidades de aves no sul do Brasil - Becker, Rafael Gustavo (Universidade do Vale do Rio do Sinos, 2009)
Mining activities cause severe alterations in natural landscapes, changing the vegetation and the properties and topography of the soil, and thus altering habitats and the associated fauna. To minimize the effects of mining, mining companies implement procedures of environmental recuperation demanded by law. The present study investigates the influence of vegetation structure on bird communities in reclaimed areas after mining in forest and grassland habitats in south Brazil. Forested areas were studied in the State of Paraná, while grasslands were studied in the Pampa biome in Rio Grande do Sul. In Paraná I sampled four areas, three of them (with 5, 10 and 20 years of vegetation recuperation named, respectively, A05, A10, and A20), were located in the Unit of Petrobrás, and the fourth was a forest fragment that did not suffer mining interferences (A50). In Rio Grande do Sul I selected six areas, three with native vegetation never mined before and three reclaimed areas. I sampled the avifauna using the point
Communities of birds and influence of the structure of the vegetation in reclaimed areas after mining in the south of Brazil
Keywords: comunidade de aves; restauração de habitat; áreas recuperadas pós-mineração; bird communities; habitat restoration; reclaimed areas; Ciências Biológicas